Pancreatic Cancer: Updates on Translational Research and Future Applications - Sarris, Evangelos G; Syrigos, Konstantinos N; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2013)
Pancreatic cancer is one of the most lethal malignancies with a mortality rate almost equal to its incidence. It is ranked as the fourth leading cause of cancer-related deaths in the United States, and despite intensive basic and clinical research over the last few years, the survival benefit for the majority of patients with pancreatic cancer is still disappointing. Due to the absence of specific symptoms and the lack of early detection tests, pancreatic cancer is usually diagnosed at an advanced inoperrable stage and palliative chemotherapy with the purine analogue gemcitabine in combination with the targeted agent erlotinib, remains the mainstay method in the management of these patients. Therefore, there is an imperative need for new findings in the translational research field with prognostic, predictive and therapeutic value. In this paper we summarize five most interesting research abstracts as presented at the 2013 American Society of Clinical Oncology (ASCO) Gastrointestinal Cancers Symposium. In particular, we focus on Abstract #141 which investigates the interaction between liver and pancreatic organ damage in patients with pancreatic cancer and the potential contribution of the patatin-like phospholipase domain containing 3 (PNPLA3) gene variation in pancreatic cancer development and on Abstract #149, in which, the prognostic and predictive role of SWI/SNF complex, a chromatin-remodeling complex, is examined. The key role of pharmacogenomics, in terms of predicting response and resistance to chemotherapy in pancreatic cancer patients, is analyzed in Abstract #142 and the contribution of circulating tumor cell detection in the early diagnosis of pancreatic cancer, allowing the avoidance of more invasive procedures like EUS-FNA, is discussed in Abstract #157. Lastly, in Abstract #164, the diagnostic utility of YKL-40 and IL-6 in pancreatic cancer patients is investigated. Image: "Sotiria" ("Salvation") General Hospital. Athens, Greece.